Prevalence and distribution of ultrasound-detected hand synovial abnormalities in a middle-aged and older population - Jiang, Ting; Yang, Tuo; Zhang, Weiya; Doherty, Michael; Zhang, Yuqing; Zeng, Chao; Sarmanova, Aliya; Yang, Zidan; Li, Jiatian; Wang, Yilun; Wang, Yuqing; Obotiba, Abasiama D.; Lei, Guanghua; Wei, Jie (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Objective Synovial abnormalities are modifiable targets for hand pain and osteoarthritis. We examined the prevalence and distribution of ultrasound-detected hand synovial abnormalities in a community-derived sample of older people in China.Methods Within the Xiangya Osteoarthritis Study, a community-based study, we assessed synovial hypertrophy (SH), joint effusion, and Power Doppler signal (PDS) on all fingers and thumbs of both hands using standardized ultrasound examinations (score: 0–3). We assessed distribution patterns of SH and effusion using χ2-test and interrelationships of SH and effusion in different joints and hands by generalized estimating equations.Results Among 3,623 participants (mean age: 64.4 years; women: 58.1%), prevalence of SH, effusion and PDS were 85.5%, 87.3% and 1.5%, respectively. Prevalence of SH, effusion and PDS increased with age, was higher in the right hand than in the left hand and was more common in proximal than in distal hand joints. SH and effusion often occurred in multiple joints (P < 0.001). SH in one joint was strongly associated with presence of SH in the same joint of the opposite hand (odds ratio [OR]= 6.60, 95% confidence interval [CI]: 6.19–7.03) followed by SH in other joints in the same row, (OR=5.70, 95%CI: 5.32–6.11), and then other joints in the same ray of the same hand (OR=1.49, 95%CI: 1.39–1.60). Similar patterns were observed for effusion.Conclusion Hand synovial abnormalities are common among older people, often affect multiple hand joints and present a unique pattern. These findings suggest both systemic and mechanical factors play roles in their occurrence.
Keywords: Synovial abnormalities; Hand; Prevalence; Distribution; Ultrasonography